2010
DOI: 10.1007/s10509-010-0578-5
|View full text |Cite
|
Sign up to set email alerts
|

The fallacy of Oppenheimer Snyder collapse: no general relativistic collapse at all, no black hole, no physical singularity

Abstract: By applying Birkhoff's theorem to the problem of the general relativistic collapse of a uniform density dust, we directly show that the density of the dust ρ = 0 even when its proper number density n would be assumed to be finite! The physical reason behind this exact result can be traced back to the observation of Arnowitt et al. (Phys. Rev. Lett. 4: 375, 1960) that the gravitational mass of a neutral point particle is zero: m = 0. And since, a dust is a mere collection of neutral point particles, unlike a c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
7
0
2
Order By: Relevance
“…Very recently, the Event Horizon Telescope has imaged a plasma jet coming out from a region within In reality, even by mundane classical GTR, as we found here, there is no finite mass BH [28,31,32,47,48] there is no EH, no EH thermodynamics (except area A = 0, and entropy S = 0), no "Hawking Radiation", and no voodoo "Firewall" [2,3,23,28,31,47]. Further instead of fictitious quantum gravitational "Hawking Radiation" or preHawking radiation, any gravitational collapse is accompanied by well understood radiation in the form of photons and neutrinos for which no unfounded QG is required [1][2][3][21][22][23]36].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Very recently, the Event Horizon Telescope has imaged a plasma jet coming out from a region within In reality, even by mundane classical GTR, as we found here, there is no finite mass BH [28,31,32,47,48] there is no EH, no EH thermodynamics (except area A = 0, and entropy S = 0), no "Hawking Radiation", and no voodoo "Firewall" [2,3,23,28,31,47]. Further instead of fictitious quantum gravitational "Hawking Radiation" or preHawking radiation, any gravitational collapse is accompanied by well understood radiation in the form of photons and neutrinos for which no unfounded QG is required [1][2][3][21][22][23]36].…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, the exact solutions associated with the collapse of this homogeneous sphere too vacuous as they correspond to 0   [41]. And the collapse of a homogeneous pressure-less collapse (the OS collapse) too is vacuous because it corresponds to 0   [28,29]. As recently found, one of the most important metrics in GR, namely the de-Sitter metric, which is the basis for supposed "cosmic inflation" and "dark energy" is illusory because, for self-consistency, one must have cosmological constant 0   [42].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In fact, the OS collapse is a mathematical illusion because, as revealed by the Birkhoff's theorem, it corresponds to ρ = M = 0. 7 In general, BH solutions represent asymptotic static states of continued gravitational collapse which are never realized at any finite proper time. In any case, BH solutions implicitly correspond to M = 0 implying that entire mass-energy must be radiated away asymptotically during continued collapse.…”
Section: Discussionmentioning
confidence: 99%
“…To further appreciate the fact how some of the exact solutions could be physically misleading, recall the case of the celebrated Oppenheimer-Snyder solution which has been considered as the ultimate proof that GR allows formation of "Black Holes" (BH). But now it has been shown that, this solution is only a mathematical illusion, it does not really imply any BH/singularity formation because a strict fluid has = 0 p = 0  too [4]. Similarly, by using this coordinate freedom of choosing time coordinate in GR and by directly integrating the part of the local energy momentum conservation equation:…”
Section: Introductionmentioning
confidence: 98%